2019
DOI: 10.1002/jcop.22310
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a brief RNR‐based training on Turkish juvenile probation officers' punitive and rehabilitative attitudes and recidivism risk perceptions

Abstract: The present quasi‐experimental study examined the impact of a brief training program based on the risk–need–responsivity (RNR) model on Turkish juvenile probation officers' (JPOs) punitive and rehabilitative attitudes toward justice‐involved youth and recidivism risk perceptions. Fifty‐nine JPOs were recruited through three probation offices in Istanbul, Turkey. Thirty‐six JPOs, who received a 1‐day training in the RNR model of offending behavior, were compared to JPOs in a wait‐list control condition (n = 23)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Indeed, we believe that identifying the aim of the system as "rehabilitation" or "law enforcement" by policy makers is a crucial step to give way to other changes. Without this clarity, even the trainings to enhance rehabilitative attitudes of POs fail because of the incompatibility between the aim of these efforts and the expectations of the system (Tuncer, Erdem, & de Ruiter, 2018). It may also be the reason for the hierarchical nature of the probation system because the lack of clarity of expectations impedes POs' attempts to take the initiative and increase the likelihood of relying on their supervisors' decisions about their cases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we believe that identifying the aim of the system as "rehabilitation" or "law enforcement" by policy makers is a crucial step to give way to other changes. Without this clarity, even the trainings to enhance rehabilitative attitudes of POs fail because of the incompatibility between the aim of these efforts and the expectations of the system (Tuncer, Erdem, & de Ruiter, 2018). It may also be the reason for the hierarchical nature of the probation system because the lack of clarity of expectations impedes POs' attempts to take the initiative and increase the likelihood of relying on their supervisors' decisions about their cases.…”
Section: Discussionmentioning
confidence: 99%
“…Depersonalization in itself may be viewed as a strategy to cope with the emotional burden of the work and thereby exacerbate negative attitudes toward probationers. Prior research has shown that Turkish POs, despite many complaints, feel hopeless about changing the probation system and report a lack of access to resources (Aslanyürek Zorlu, 2014 ; Erdem et al, 2019 ; Tuncer et al, 2020 ). That is, officers have little input into decision‐making and lack opportunities for training and supervision, factors that are significantly associated with depersonalization (Rhineberger‐Dunn & Mack, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown positive associations between probationer success and improved interpersonal relationships between POs and probationers (e.g., collaborative communication; Kleinpeter et al, 2011 ; positive alliance; Clark et al, 2006 ). Future research could examine whether interventions that improve the quality of relationships between POs and probationers translate to more favorable attitudes toward probationers and decreased levels of job burnout (Gayman et al, 2018 ; Tuncer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations